2002
DOI: 10.1002/hup.367
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine augmentation in risperidone‐resistant schizophrenia: an open trial

Abstract: We investigated the efficacy and safety of augmenting risperidone with fluvoxamine for the treatment of residual positive and negative symptoms in patients with chronic schizophrenia who had shown an incomplete response to risperidone. A total of 30 patients completed the open trial over a 12-week period during which fluvoxamine was added to risperidone. The result from the positive and negative syndrome scale (PANSS) and Simpson-Angus extrapyramidal effects (S-A) scale were examined at baseline, 1, 2, 4, 8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Silver et al 36,37 reported that fluvoxamine add-on therapy improved negative symptoms of patients with chronic schizophrenia who received typical or atypical antipsychotics. Takahashi et al 71 reported that fluvoxamine appeared to be ineffective on the PANSS scores in augmenting the risperidone treatment response in chronic schizophrenic patients. 70 In addition, fluvoxamine addon therapy did not improve the PANSS scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver et al 36,37 reported that fluvoxamine add-on therapy improved negative symptoms of patients with chronic schizophrenia who received typical or atypical antipsychotics. Takahashi et al 71 reported that fluvoxamine appeared to be ineffective on the PANSS scores in augmenting the risperidone treatment response in chronic schizophrenic patients. 70 In addition, fluvoxamine addon therapy did not improve the PANSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis demonstrated no global support for an improvement in negative symptoms with SSRI augmentation therapy in schizophrenia. 36,37,71 However, 1 patient who had previously received olanzapine medication deteriorated with regard to positive symptoms in the follow-up phase, but not in the add-on phase. Takahashi et al 71 reported that fluvoxamine appeared to be ineffective on the PANSS scores in augmenting the risperidone treatment response in chronic schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…(Ellingrod et al 2002) Poor metabolizers given antipsychotics with limited dose ranges are more prone to adverse effects, while ultrarapid inducers will not respond to normal antipsychotic doses. Several research studies have looked into the significance of CYP2D6 genetic polymorphism in developing side effects, particularly EPS, following antipsychotic medication (Takashi et al 2002). PMs on risperidone have a three-fold higher chance of having harmful effects than EM or IM patients.…”
Section: Cyp2d6mentioning
confidence: 99%